Lateral crural overlay of the lower lateral cartilages, a technique to enhance nasal tip rotation, and reduce projection in the droopy nasal tip - Abdilkarim, Dana A. (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Tip plasty is one of the most common feats encountered by the Aesthetic Rhinoplasty Surgeon. Tip rotation, with or without tip deprojection, is one of the challenging problems that face the surgeon, with many overwhelming techniques to correct rotation and projection of the nasal tip, including, but not limited to overlapping of the lateral crural cartilages. This study aimed to assess the efficacy and reliability of the technique of the lateral crural overlay of the lower lateral cartilages in enhancing nasal tip rotation and decreasing nasal tip projection. Methods: This prospective study included 64 patients, who underwent primary, and secondary, open Rhinoplasty, with nasal droopy tip and nasal tip true overprojection problems. They have been treated in Sulaimaniyah Hospital for Burn and Plastic Surgery, and from Private Hospitals in Sulaimaniyah city. The age range was 18-34 years. Forty nine patients were female, the rest of the patients were male. They have been treated, primarily, for the tip drooping and to a lesser extent for nasal tip overprojection, by the senior author, with Lateral Crural Cartilages Overlay. The study conducted from April 2012 to January 2016. The patients, postoperatively, were followed up for up to one year. Goode ratio and Nasofacial angle deducted from real time photographs have been used to evaluate the amount of rotation and deprojection of the nasal tip. Results: Overlapping of the Lateral Crura of the Lower Lateral Cartilages, is a safe and reasonable technic in achieving nasal tip rotation, with or without, projection reduction, of the droopy nose. The operative time and dissection are very encouraging. Complications associated with this technic are very negligible, with high patient satisfaction rates. Only five rhinoplasty patient has been revised for the sake of tip rotation/projection, in this series of cases. No Major complications happened in the collumellar skin incision or the nasal rim infracartilagenous incisions, nor in the undermined nasal vestibular skin separated from the undersurface of the Lower Lateral Cartilages. Conclusion: Overlapping, or overlaying, of the lateral crura of the lower lateral cartilages, is a reasonable technique to enhance tip rotation, and reduction of the tip projection, by medial crural steal and telescoping of the incised lower lateral cartilages, with good aesthetic and functional outcomes, with reasonable complication rates, very low revision rate, and high patient satisfaction rates.